High sensitivity troponin I and T reflect the presence of obstructive and multi-vessel coronary artery disease being assessed by coronary computed tomography angiography - Reckord, Nadine; Behnes, Michael; Natale, Michèle; Mukherji, Agnibh; Ansari, Uzair; Lang, Siegfried; Hoffmann, Ursula; Borggrefe, Martin; Henzler, Thomas; Neumaier, Michael; Kittel, Maximilian; Akın, Ibrahim (Current pharmaceutical biotechnology, 2017)
Background: This study evaluates the association between high sensitivity troponin I (hsTnI) and T (hsTnT) in patients with suspected stable Coronary Artery Disease (CAD) undergoing Coronary Computed Tomography Angiography (CCTA). Methods: Patients undergoing CCTA were enrolled prospectively. CCTA was indicated in patients with angina and a low to intermediate pre-test probability for CAD during routine clinical care. Blood samples were taken at the time of CCTA to measure cardiac biomarkers. Results: A total of 99 patients were enrolled with 43 % revealing no CAD, 30 % with non-obstructive and 26 % with obstructive CAD. Out of these, 61 % had single-vessel and 39 % had multi-vessel CAD. Both hsTnI and hsTnT levels increased significantly according to the presence and extent of CAD (p = 0.0001) and were able to discriminate the presence of both obstructive (AUC range: 0.775 - 0.785; p = 0.0001) and multi-vessel CAD (AUC range: 0.740 - 0.749; p = 0.01). In multivariate logistic regression models adjusted for cardiovascular risk factors and NT-proBNP, both hsTn were still associated significantly with obstructive CAD (range of odds ratios (OR): 8.3-32.3; p < 0.02). Discussion: This study shows that high sensitivity troponin I and T reflect the presence and extent of CAD being diagnosed by CCTA in patients with a low to intermediate pretest probability for CAD.